2017
DOI: 10.1088/1361-6528/aa60fd
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible chitosan nanoparticles as an efficient delivery vehicle forMycobacterium tuberculosislipids to induce potent cytokines and antibody response through activation ofγδT cells in mice

Abstract: The activation of cell-mediated and humoral immune responses to Mycobacterium tuberculosis (Mtb) is critical for protection against the pathogen and nanoparticle-mediated delivery of antigens is a more potent way to induce different immune responses. Herein, we show that mice immunized with Mtb lipid-bound chitosan nanoparticles (NPs) induce secretion of prominent type-1 T-helper (Th-1) and type-2 T-helper (Th-2) cytokines in lymph node and spleen cells, and also induces significantly higher levels of IgG, IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 50 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…The delivery of PLGA and chitosan NP conjugated vaccine molecules enhanced the immune responses at the mucosal site ( 95 , 96 ). Our recent study also showed that delivery of M. tuberculosis lipids using biocompatible chitosan NPs was able to induce significant humoral as well as cellular immune responses when compared to lipids alone in mice ( 43 ). We also found that intraperitoneal administration of these conjugates showed better activation of splenic T-cells.…”
Section: Types Of Nano-immuno Activatorsmentioning
confidence: 95%
“…The delivery of PLGA and chitosan NP conjugated vaccine molecules enhanced the immune responses at the mucosal site ( 95 , 96 ). Our recent study also showed that delivery of M. tuberculosis lipids using biocompatible chitosan NPs was able to induce significant humoral as well as cellular immune responses when compared to lipids alone in mice ( 43 ). We also found that intraperitoneal administration of these conjugates showed better activation of splenic T-cells.…”
Section: Types Of Nano-immuno Activatorsmentioning
confidence: 95%
“…boost (Esat-6/3e) Mice Decreased bacterial counts in the lungs and spleens [43] Chitosan Mycobacterium lipids i.p. Mice No results [44] Mycobacterium bovis Liposome Fusion of antigen 85b and Esat-6 s.c. Mice Decreased bacterial counts in the lungs and spleen [45] a. The better or the best route to achieve protection; b.…”
Section: Bacterial Infectious Diseases and Advanced Delivery Systemsmentioning
confidence: 99%
“…45 Exhibition of lower toxicity at longer milling time points can be explained by the presence of blended chitosan with CAS which has been reported to be biocompatible at a specific concentration. 46 It can be deduced that CAS-CH 3H, 2H, and 1H exhibited comparative biocompatibility considering the biocompatibility of CH as a threshold parameter. Moreover, CAS alone was found to be cytotoxic in this comparison.…”
Section: Discussionmentioning
confidence: 98%